Visualising the synthetic universe - Haydon, Daniel T. (2020)
Star formation cannot truly be understood from observational data alone; only with simulations is it possible to assemble the complete picture. Observations guide the physics we build into our simulations, yet the impact of different star formation and feedback models can only be investigated with simulations. Synthetic observations allow us to make a realistic comparison to true observations as well as teach us about the emission tracers we depend upon. Through coupling the stellar population synthesis code SLUG2 to galaxy simulations, we can generate synthetic star formation rate tracer maps. These maps assume different stellar metallicities, star formation rate surface densities, and suffer from varied amounts of extinction. This allows us to explore and constrain the environmental effects on the characteristic emission lifetimes — the duration for which a tracer is visible. With these emission lifetimes and in conjunction with a new statistical method, the ‘uncertainty principle for star formation’, constraints can be placed upon the durations of different evolutionary phases of the star formation process, allowing us to better understand the physics of star formation and feedback on sub-galactic scales. Studying the interstellar medium can also reveal information about stellar feedback: the gas density structure is altered as a result of the injected energy, momentum, and matter. Surveys of the CO emission in galaxies can tell us how the properties of this medium have evolved over cosmic time. Using DESPOTIC to model CO line emission of gas found within the IllustrisTNG50 cosmological simulation, we produce an equivalent synthetic survey. This synthetic survey can be used as a basis for comparison and predictor of observational trends.